Anti-obesity action of INDUS810, a natural compound from Trigonella foenum-graecum: AMPK-dependent lipolysis effect in adipocytes. Issue 6 (November 2018) - Cheng, Ching-Yuan; Yang, Ai-Jen; Ekambaranellore, Prakash; Huang, Kuo-Chin; Lin, Wan-Wan
Graphical abstract: Abstract: Objective: We investigated the anti-obesity effect and underlying action mechanism of INDUS810 isolated from Trigonella foenum-graecum L. ( Fabaceae ), an annual herb commonly known as fenugreek and reported to have hypocholesterolemic, antidiabetic, anticancer and gastroprotective properties. Methods: For obese animal study, 4-week old mice were fed with normal diet or high-fat diet together with or without intraperitoneal injection of INDUS810 (200 mg/kg) twice per week for 15 weeks. 3T3-L1 cells were used to study action mechanism of INDUS810 in adipocyte differentiation and lipid metabolism. Results: We found that INDUS810 can reduce high-fat diet-induced weight increase in epididymal white adipose tissue, interscapular brown adipose tissue and liver, as well as serum levels of total cholesterol and low-density lipoprotein cholesterol. Moreover, the insulin sensitivity was significantly improved in INDUS810-treated obese mice. In 3T3-L1 adipocytes, we found that INDUS810 could inhibit lipid accumulation at either differentiating or mature stages, and increase lipolysis activity in mature adipocytes. Additionally, INDUS810 has no effects on cell viability nor the expressions of adipocyte differentiation markers like fatty acid synthase, peroxisome proliferator-activated receptor γ and CCAAT/enhancer-binding protein α. In contrast, INDUS810 can increase protein levels of peroxisome proliferator-activated receptor α, peroxisome-proliferator-activated receptor-γ co-activator 1β, sirtuin 1 and sirtuin 3. Of note, INDUS810 can activate adenosine monophosphate-activated protein kinase, which leads to the reduction of lipid contents in adipocytes. Conclusion: Our in vitro and in vivo studies suggest that INDUS810 is a potential anti-obesity agent, and this action depends on activate adenosine monophosphate-activated protein kinase activation.